Pemanfaatan Pupuk Organik Cair (POC) Limbah Ternak dalam Meningkatkan Kesuburan Lahan Sayur di Desa Muara Danau - Agus Nuramal; Delon Ananda Yahya Harianja; Muhammad Raihan Palovi; Wiwin Lestari; Maynaldo sinaga; Anis Syarifatul Mursyidah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The dependence of vegetable farmers in Muara Danau Village on chemical fertilizers is quite high, while the animal waste owned by almost all residents is just left to pile up around the pens. This community service activity aims to provide training to vegetable farmer groups and local livestock farmers on how to make liquid organic fertilizer from a mix of cow, goat, and chicken manure using a participatory approach. This includes assessing needs, socialization, hands-on training, guidance at demonstration plots, and evaluation. The liquid organic fertilizer is made by adding rice washing water, palm sugar or molasses, and the EM4 bioactivator, then fermenting it anaerobically for two to three weeks. The results of the activity showed a significant increase in participants’ understanding compared to the pre-test and post-test scores, especially regarding the amount of ingredients and product maturity indicators.Trials on demonstration plots of water spinach and mustard greens also showed that plant growth and soil conditions were better in plots given liquid organic fertilizer compared to control plots given chemical fertilizer. Some challenges faced during implementation included limited fermentation containers, the community’s old habits that hadn’t fully adapted yet, and weather impacts affecting fermentation consistency. This activity proves that livestock waste can be utilized to make quality liquid organic fertilizer and has the potential to be developed into a farmer group business.